Implementation of a Poverty and Hunger-Free Village as a Realization of the SDGs - Warsono, Warsono; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Poverty and hunger are complex issues targeted by the Sustainable Development Goals (SDGs). Specific Background: Sumorame Village, Candi District, Sidoarjo Regency, implements programs aimed at poverty and hunger alleviation, focusing on collaboration and resource management. Knowledge Gap: Prior studies have not deeply explored implementation aspects at the village level within the SDGs framework. Aims: This study analyzes the implementation of poverty alleviation programs in Sumorame Village, focusing on communication, resources, disposition, and bureaucratic structure. Results: The findings indicate that effective communication and competent human resources are crucial for success. Financial resources are appropriately allocated, though infrastructure remains inadequate. Positive attitudes and strong commitment enhance program effectiveness, while the bureaucratic structure follows proper procedures. Novelty: This study provides an in-depth examination of poverty alleviation in the village context, highlighting the role of communication and resource management. Implications: Regular evaluations of physical resources and infrastructure maintenance are necessary for sustainable poverty reduction. This research offers insights for policymakers and local governments in similar settings. Highlights: Communication: Effective communication with residents is vital for the success of poverty alleviation programs. Resource Allocation: Proper budgeting and competent human resources enhance the program's impact but infrastructure improvements are still needed. Bureaucratic Structure: Adhering to standard operating procedures and defining roles supports program implementation. Keywords: Poverty, Hunger, SDGs, Village Implementation, Resource Management